Waste tyres pyrolysis oil (WTPO) as an alternative source of fuel and chemicals: a review - Bashir Abdu Muzakkari; Amina Salihi Bayero; Musa Ibrahim Mohammed; Pramod K. Singh; Umar Muhammad Jibreel (Zaštita Materijala)
Waste tyres are dumped and common kind of abandon solid waste. Almost 3 billion tyres are produced each year and each tyre produced will eventually join the waste products and if not properly handled will become pollutant. In many countries disposal of waste tyres is prohibited; as an alternative they should be recovered and recycled instead. In this review pyrolysis was introduced as an alternative way of recycling waste tyres, Pyrolysis allows the dissolution of the waste and it also produces useful by-products. The products obtained during the process are pyrolysis oil, pyrolysis char and condensable gas. Pyrolysis oil is the major product among them, this paper reviewed pyrolysis oil as an alternative sources of fuel to diesel engines and as well to highlight the chemicals obtained in the waste tyres from the pyrolysis oil which mainly depends on the kind of feedstock (i.e. type of tyres e.g truck, cars, bicycle) used in the pyrolysis process. Most of the compounds obtained are Aliphatic and Aromatic hydrocarbons (especially the Polycyclic Aromatic Hydrocarbon PAHs) such as Naphthalene – NAP, Acenaphthylene – ACY, Acenaphthene –ACE, Fluorene – FLU, Phenanthrene – PHE, Anthracene – ANT, Fluoranthene–FLT, Pyrene–PYR, Benzo[a]anthracene – BAA, Chrysene – CRY, Benzo[b]fluoranthene – BBF, Benzo[k[fluoranthene – BKF, Benzo[a]pyrene – BAP, Dibenzo[a,h]anthracene – DBA, Benzo[g,h,i]perylene – BGP, Indeno[1,2,3-cd]pyrene – IND among others. Consequently, the pyrolysis oil obtained need further upgrading via a reaction pathways are hydrodesulfurization (HDS), hydrodearomatization (HDA) and hydrocracking (HC) which can be achieved through a 2-stage hydroprocessing strategy regarding WTPO composition in terms of HDS, HAD and HC. Pyrolysis oil from waste tyres can be used as a substitute for diesel and as well as sources of raw materials and fuel to organic chemical industries.